TINJAUAN SOSIOLOGIS NOVEL DI KAKI BUKIT CIBALAK KARYA AHMAD TOHARI - Roch Widjatini (Jurnal Lingua Idea, 2018)
The rural condition as the background with the second grade society that became the main power of Ahmad Tohari’s story has encourage the scientist and literary community place this story as the main topic. The study about Di Kaki Bukit Cibalak needs to be done in order to observe Ahmad Tohari potention as a writer. The problem that shown could be explain as this question, how about the situation and the social change process that found in Di Kaki Bukit Cibalak, and how about the people’s react against that social change condition